Research on Motion Control Optimization of Quadruped Crawling Robot for Continuous Slope - Zhang, Peng; Wang, TianYu; Dong, Ren Q.; Liu, XiuLian; Wang, Peng (Recent Patents on Engineering, 2024)
Background: In recent years, literature has suggested that quadruped crawling robots have been widely used in the field of reconnaissance on rugged mountain trails. Under the influence of gait and slope, the joint angle of the robot changes drastically when landing, resulting in the robot drop down from the slope. This has strict requirements for gait planning and gait control of quadruped crawling robots. Objective: The aim of this study is to set up a novel impedance controller based on gearshift integral PID to improve the stability of a quadruped crawling robot during climbing on a continuous slope. Methods: The three-dimensional model of quadruped crawling robot was established. Considering the characteristics of slope terrain, a slope diagonal gait design is proposed, and a gearshift integral PID impedance controller is designed for this gait. The impedance controller based on position PID, integral separation PID and gearshift integral PID is simulated by MATLAB, and the peak value of foot force is compared under ADAMS. Results: Overshoot and transient time of positional PID impedance controller was compared, integral separated PID impedance controller and gearshift integral PID impedance controller, the overshoot was reduced by 8.9% and the transient time was reduced by 20%. Finally, the position impedance controller that meets the requirements and import it into ADAMS to compare the peak foot force was selected, it reduced the foot-end contact force by 8.15%.The results show that the gearshift integral PID impedance control strategy is feasible. Conclusion: The Impedance controller based on gearshift integral PID can provide a reference for other impedance control strategies of quadruped crawling robots.
Keywords: comparative simulation analysis of controller